2022
DOI: 10.1038/s41416-022-02029-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between angiotensin-converting enzyme inhibitors and the risk of lung cancer: a systematic review and meta-analysis

Abstract: Background The association between the use of angiotensin-converting enzyme inhibitors (ACEIs) and lung cancer risk remains controversial. This study evaluated the association between the use of ACEIs and lung cancer risk. Methods Records from five databases were searched from inception to 26 January 2022. Clinical studies involving persons aged ≥18 years with at least one year of follow-up and reporting adverse events, including lung cancer, were recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 57 publications
0
13
1
1
Order By: Relevance
“…Recent clinical studies have shown that lung cancer is a notable adverse event attributable to ACEI use ( Hicks et al, 2018 ; Lin et al, 2020 ; Kristensen et al, 2021 ). A recent meta-analysis ( Wu et al, 2023 ) by the authors of the present study (Wu and Yao) demonstrated that ACEI use is a greater risk factor for lung cancer (up to 1.6%) than angiotensin receptor blocker use, especially among Asian patients.…”
Section: Introductionmentioning
confidence: 48%
“…Recent clinical studies have shown that lung cancer is a notable adverse event attributable to ACEI use ( Hicks et al, 2018 ; Lin et al, 2020 ; Kristensen et al, 2021 ). A recent meta-analysis ( Wu et al, 2023 ) by the authors of the present study (Wu and Yao) demonstrated that ACEI use is a greater risk factor for lung cancer (up to 1.6%) than angiotensin receptor blocker use, especially among Asian patients.…”
Section: Introductionmentioning
confidence: 48%
“…Somatic ACE arose as an implication of gene duplication and contains two active sites (Terminal N-and C-domains). The polypeptide chain of somatic ACE is 1,277 amino acids, whereas the testicular ACE is smaller with 701 amino acid residues [63].…”
Section: Angiotensin-converting Enzyme (Ace)mentioning
confidence: 99%
“…Somatic ACE (sACE) has a significant role in the blood pressure regulatory mechanism (renin-angiotensin system). In somatic ACE, the polypeptide chain is 1,277 amino acids in length [63]. It is involved in the Ang II formation which is a potent vasoconstrictor and also degrades the vasodilator bradykinin, thereby resulting in increased blood pressure [64].…”
Section: Somatic Acementioning
confidence: 99%
See 1 more Smart Citation
“…The role of angiotensin system inhibition (ASI) in modifying the risk of developing lung cancer has been an area of intense study, with important implications should this common class of drugs be found to promote lung cancer. 1 , 2 , 3 , 4 Comparatively little study has been done into the influence ASI may have on treatment of an established lung cancer. Several small retrospective studies have demonstrated a 40% increase in survival in patients incidentally receiving ASI versus those not exposed to ASI and a 47% increase in progression-free survival with ASI use, which was most pronounced with angiotensin receptor binders therapy.…”
mentioning
confidence: 99%